Associations of KLOTHO-VS heterozygosity and α-Klotho protein with cerebrospinal fluid Alzheimer's disease biomarkers - Katonova, Alzbeta; Andel, Ross; Jurasova, Vanesa; Veverova, Katerina; Angelucci, Francesco; Matoska, Vaclav; Hort, Jakub (Journal of Alzheimer's disease, 2025)
BackgroundKLOTHO-VS heterozygosity (KL-VSHET) and soluble α-Klotho (sαKl) protein interfere with Alzheimer's disease (AD) pathophysiology, but the specific relationships remain unclear. This study explored these associations across the AD continuum, focusing on core AD biomarkers and markers of neurodegeneration, neuroinflammation, and synaptic dysfunction.ObjectiveWe investigated whether 1) KL-VSHET is associated with lower AD biomarker burden (Aβ42, Aβ42/40 ratio, P-tau181, T-tau) and neurodegeneration (NfL); 2) sαKl relates to AD biomarkers, neurodegeneration (NfL), neuroinflammation (GFAP), and synaptic dysfunction (Ng); 3) associations vary by APOE ε4 status and clinical subgroup.MethodsParticipants (n = 223) were categorized as cognitively healthy (n = 38), aMCI-AD (n = 94), and AD dementia (n = 91). KLOTHO genotyping was available for 128 participants; 138 had cerebrospinal fluid (CSF) and serum sαKl measurements; and 42 had both. Multiple linear regression evaluated associations between KL-VSHET, sαKl levels, and biomarkers, stratified by APOE ε4 status and clinical subgroup.ResultsOverall, the associations between KL-VSHET and higher CSF Aβ42 and Aβ42/40 ratio were non-significant (ps ≥ 0.059) except when restricted to APOE ε4 carriers only (β = 0.11, p = 0.008 and β = 0.16, p = 0.033, respectively). Within clinical subgroups, KL-VSHET was positively associated with Aβ42/40 ratio only in aMCI-AD (β = 0.23, p = 0.034). No significant associations were observed between KL-VSHET and tau biomarkers or NfL. For sαKl, associations with biomarkers were non-significant except for a negative association of serum sαKl with P-tau181 in aMCI-AD (β = -0.25, p = 0.036) and a positive association with Aβ42/40 ratio in APOE ε4 non-carriers (β = 0.24 p = 0.047).ConclusionsKL-VSHET may help protect against amyloid pathology, particularly in the presence of APOE ε4, and regardless of APOE status in aMCI-AD.
Keywords: Klotho Proteins; KLOTHO-VS heterozygosity; heterozygot; α-Klotho; Female; Cognitive Dysfunction; biologické markery; Amyloid beta-Peptides; tau Proteins; APOE; Biomarkers; ženské pohlaví; lidé; apolipoprotein E4; amyloidní beta-protein; Heterozygote; Aged, 80 and over; peptidové fragmenty; Apolipoprotein E4; Alzheimer's disease; Male; Peptide Fragments; Aged; Alzheimer Disease; kognitivní dysfunkce; Alzheimerova nemoc; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; biomarkers; glukuronidasa; proteiny Klotho; Glucuronidase; Middle Aged; proteiny tau; Humans